A method for forming thermal expansion protrusions and ring-shaped molten structures on a sapphire surface by CO2 laser irradiation

CN122913680APending Publication Date: 2026-10-16NANJING UNIV OF SCI & TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610779431.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-06-02
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

对于微秒量级CO2激光辐照蓝宝石的热熔效应,尤其是激光诱导的热膨胀凸起与环形熔融共存结构的形成机理与控制方法,缺乏系统研究

Benefits of technology

[0016] 1) For the first time, controllable processing of thermal expansion protrusions and annular melting depressions at the center of sapphire surface has been achieved, enriching the means of laser surface microstructure preparation and applicable to scenarios such as microlens arrays, annular gratings, and laser energy homogenization.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122913680A_ABST
    Figure CN122913680A_ABST
Patent Text Reader

Abstract

The application discloses a method for forming a central thermal expansion protrusion and a ring-shaped melting structure on a sapphire surface by CO2 laser irradiation, wherein a pulsed CO2 laser with a wavelength of 10.6 microns is vertically irradiated on a single crystal sapphire surface; the repetition frequency is adjusted to 1000-4000 Hz, the peak power is adjusted to 42-85 W, the duty cycle is adjusted to 20%-40%, and the irradiation time is adjusted to 1-5 s, so that a central thermal expansion protrusion and a ring-shaped melting depression are formed on the surface. The morphology is observed by an optical microscope and a white light interferometer; a two-dimensional axisymmetric model is established, a thermal-solid and thermal-flow coupling model is constructed, a temperature field, a stress field and a Navier-Stokes equation are solved, and the simulation morphology is compared and verified with the experiment. The application realizes controllable formation of a thermal expansion protrusion and a ring-shaped melting depression on a sapphire surface, reveals a thermal-force-flow coupling mechanism in combination with simulation, and can be used for optical elements such as a microlens array and a ring-shaped grating.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to laser processing and optical material processing technology, specifically to a method for forming thermally expanded protrusions and annular molten structures on the surface of sapphire by CO2 laser irradiation. Background Technology

[0002] Sapphire (Al2O3) single crystals possess high hardness, high melting point, broad spectral transmittance, and excellent chemical stability, making them widely used in infrared windows, LED substrates, and precision optical components. However, sapphire is a typical hard and brittle material, and traditional machining methods easily result in damage such as cracks and chipping. CO2 lasers (wavelength 10.6μm) have significant potential in the thermal processing of sapphire due to their high energy utilization and controllable thermal effects.

[0003] Existing research on laser processing of sapphire largely focuses on nanosecond, picosecond, and femtosecond lasers, primarily addressing ablation thresholds, micro-hole fabrication, and surface smoothness. Systematic studies are lacking on the thermal melting effect of sapphire irradiated by microsecond-level CO2 lasers, particularly the formation mechanism and control methods of laser-induced thermal expansion protrusions and coexisting annular molten structures. Furthermore, experiments alone are insufficient to reveal the transient evolution of temperature, stress, and molten pool flow during laser irradiation; in-depth analysis combining numerical simulations is necessary.

[0004] Therefore, there is an urgent need in this field for a method that can controllably form thermal expansion protrusions and ring-shaped molten structures on the surface of sapphire by adjusting the parameters of CO2 laser, and to establish a corresponding simulation model to guide process optimization. Summary of the Invention

[0005] The purpose of this invention is to provide a method for forming thermally expanded protrusions and annular molten structures on the surface of sapphire by CO2 laser irradiation.

[0006] The technical solution to achieve the purpose of this invention is as follows: a method for forming a central thermal expansion protrusion and an annular melting depression on the surface of sapphire by CO2 laser irradiation, comprising the following steps:

[0007] A pulsed CO2 laser with a wavelength of 10.6 μm was used to focus the laser beam and irradiate it vertically onto the surface of a single-crystal sapphire sample. The repetition frequency of the laser was adjusted to 1000 Hz to 4000 Hz, the peak power to 42 W to 85 W, the duty cycle to 20% to 40%, and the irradiation time to 1 s to 5 s, so that a central thermal expansion protrusion and a ring-shaped melting depression were formed on the sapphire surface. The two-dimensional and three-dimensional morphology of the irradiated area was observed using an optical microscope and a white light interferometer.

[0008] A two-dimensional axisymmetric geometric model was established, and a thermo-solid coupling model and a thermo-fluid coupling model were constructed. Laser parameters and thermal property parameters of sapphire were set to be consistent with the aforementioned laser parameters. The temperature field control equation, stress field control equation and Navier-Stokes equation were solved. The morphology output by simulation was compared and verified with the morphology obtained by observation.

[0009] Furthermore, the single-crystal sapphire sample is a C-face sapphire, an A-face sapphire, or an M-face sapphire, and the sample thickness is not less than 1 mm.

[0010] Furthermore, the radius of the laser focusing spot is 0.6mm~1.0mm.

[0011] Furthermore, when the repetition frequency is 2000Hz~3000Hz, the peak power is 59W~70W, and the duty cycle is 40%, a composite structure of a central thermal expansion protrusion and a surrounding annular molten depression is formed on the sapphire surface. The height of the central thermal expansion protrusion is 20µm~45µm, and the depth of the annular molten depression is 2µm~10µm.

[0012] Furthermore, when the repetition frequency is 2000Hz, the peak power is 59W, and the duty cycle is 20%, a double-protrusion structure is formed on the sapphire surface, consisting of a central thermal expansion protrusion and a surrounding annular thermal expansion protrusion.

[0013] Furthermore, the thermo-solid coupling model is used to analyze the stress distribution during the thermal expansion stage. Calculations show that radial and circumferential stresses are dominated by compressive stress. When the temperature exceeds 1000K, the compressive stress can reach 1340MPa, which exceeds the compressive strength of sapphire at 1000K, forcing the softened material to flow upward plastically and form protrusions.

[0014] Furthermore, the heat-fluid coupling model considers the change in surface tension with temperature and the Marangoni effect, where the molten material migrates from the central high-temperature, low-surface-tension region to the edge low-temperature, high-surface-tension region, forming a molten pit morphology with a central depression and edge accumulation.

[0015] Compared with the prior art, the significant advantages of this invention are:

[0016] 1) For the first time, controllable processing of thermal expansion protrusions and annular melting depressions at the center of sapphire surface has been achieved, enriching the means of laser surface microstructure preparation and applicable to scenarios such as microlens arrays, annular gratings, and laser energy homogenization.

[0017] 2) The laser-induced thermal expansion protrusion achieves a beam self-deflection effect, redistributing the Gaussian beam energy into ring energy without a complex optical system, thereby generating ring melting at the root of the protrusion. This mechanism has been verified by both experiments and simulations.

[0018] 3) High-fidelity numerical models of thermal-solid coupling and thermal-fluid coupling were established, and the stress distribution in the thermal expansion stage and the Marangoni effect in the melting stage were systematically analyzed, revealing the physical nature of protrusion formation and crater evolution.

[0019] 4) By adjusting the laser parameters (repetition frequency, peak power, duty cycle), various morphologies such as pure thermal expansion protrusions, double protrusions, or central protrusions + ring melting can be obtained on the same material, which has the advantages of wide parameter control window and good repeatability. Attached Figure Description

[0020] Figure 1 This is a schematic diagram of the experimental apparatus of the present invention.

[0021] Figure 2 Optical microscope image of thermal expansion protrusions and ring-shaped fused structures on the surface of sapphire.

[0022] Figure 3 A 3D reconstruction image of a white light interferometer showing a central protrusion and annular thermal expansion protrusion structure on the sapphire surface.

[0023] Figure 4 The curves show the variation of the height of the sapphire ablation center under different peak powers.

[0024] Figure 5 The curves show the variation of the height of the ablation center and the diameter of the expansion region in sapphire at different repetition frequencies.

[0025] Figure 6 The temperature field and stress distribution diagrams are obtained from the simulation of the thermal expansion stage.

[0026] Figure 7 The image shows the morphology of the molten pool and the velocity field distribution obtained from the simulation of the melting stage. Detailed Implementation

[0027] To make the objectives, technical solutions, and advantages of this application clearer, the following detailed description is provided in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are merely illustrative and not intended to limit the scope of this application.

[0028] A method for forming thermally expanded protrusions and annular molten structures on the surface of sapphire by CO2 laser irradiation is based on the controllable creation of specific thermal molten morphologies on the sapphire surface through the combined use of experimental parameter adjustment and numerical simulation.

[0029] This invention achieves the target structure based on the following physical mechanism:

[0030] First, the central thermal expansion protrusion is formed. CO2 laser irradiation raises the surface temperature of sapphire to below its melting point, approximately 1000K. The thermal expansion, constrained by the surrounding cold material, generates enormous compressive stress, calculated to exceed 1340MPa, which is more than 400MPa higher than the high-temperature compressive strength of sapphire at 1000K. This causes the softened layer to plastically flow upward, forming the central thermal expansion protrusion.

[0031] Second, laser energy redistribution. The raised surface morphology deflects the subsequent laser beam, redistributing the Gaussian energy into ring-shaped energy, creating a ring-shaped high-temperature region at the root of the raised surface.

[0032] Third, the formation of annular molten depressions. The annular high-temperature zone melts the sapphire. The Marangoni effect, i.e., the decrease in surface tension as temperature increases, drives the molten material to migrate from the central high-temperature zone to the edge low-temperature zone, forming annular molten depressions with a central depression and edge accumulation. By adjusting laser parameters, including repetition frequency, peak power, and duty cycle, the height of the protrusion and the degree of melting can be controlled to achieve different morphologies such as pure protrusions, double protrusions, or protrusions with melting.

[0033] The experimental method is as follows.

[0034] Experimental system such as Figure 1 As shown, the setup includes a high-repetition-rate CO2 laser, model Coherent G-100, wavelength 10.6 μm, as well as an attenuator, a focusing lens with a focal length of 20 cm, a three-dimensional moving platform, a power meter, a photodetector, an oscilloscope, an optical microscope, and a white light interferometer. The experimental procedures are as follows:

[0035] The first step is to fix the single-crystal sapphire sample on the moving platform. The sample is a C-face sapphire with dimensions of 50mm × 20mm × 5mm.

[0036] The second step is to set the laser parameters: the repetition frequency range is 1000Hz to 4000Hz, the peak power range is 42W to 85W, the duty cycle range is 20% to 40%, the irradiation time range is 1s to 5s, and the focused spot radius range is 0.6mm to 1.0mm, with a typical value of 0.8mm.

[0037] The third step is to irradiate the sample surface vertically with a laser beam.

[0038] The fourth step is to observe the surface morphology using an optical microscope after irradiation and to obtain the three-dimensional morphology and cross-sectional lines using a white light interferometer.

[0039] Fifth, to ensure repeatability, each set of parameters was tested three times, with a spacing of 1.2 cm between adjacent irradiation points to avoid overlap of the heat-affected zone.

[0040] The simulation method is as follows.

[0041] Establish a two-dimensional axisymmetric geometric model (radius 6mm, height 2mm) and solve it in COMSOL Multiphysics software.

[0042] 1) The thermo-solid coupling model is used for the thermal expansion stage.

[0043] The temperature field governing equation adopts the classical Fourier heat conduction equation:

[0044]

[0045] In the formula, for Temperature field distribution of the sample at any given time , , These are the density, specific heat capacity, and thermal conductivity at this moment, respectively. It is the heat source of the material.

[0046] The stress field constitutive equations take into account the anisotropic linear elasticity of sapphire:

[0047]

[0048] In the formula, , , Normal stress in three directions (corresponding to the x, y, and z directions respectively). , , Shear stress in three planes (corresponding to the xy, yz, and zx planes respectively). , , : Normal strain in three directions (corresponding to the x, y, and z directions respectively). , , Shear strain in three planes (corresponding to the xy, yz, and zx planes respectively). , , , , , Where is the elastic constant.

[0049] The laser heat source has a Gaussian distribution:

[0050]

[0051] in, for Temperature field distribution of the sample at any given time Thermal conductivity, The boundary of the laser irradiation area. As a boundary heat source, It is a normal vector perpendicular to the boundary and pointing outwards.

[0052] The peak power is 59.23W, the spot radius is 0.8mm, the duty cycle is 40%, and the repetition frequency is 1000Hz.

[0053] The solid material parameters are as follows: density 3990 kg / m³ (solid), specific heat capacity 1430 J / (kg·K), thermal conductivity 5 W / (m·K), and coefficient of thermal expansion varies with temperature (at 293 K). At 1770K The elastic constants are shown in Table 1, with units of . .

[0054] Table 1 Elastic constants of sapphire

[0055]

[0056] 2) Thermal-fluid coupling model used in the melting stage

[0057] Considering the molten fluid to be an incompressible Newtonian fluid, the Navier-Stokes equations are as follows:

[0058]

[0059] in, For density, It is a velocity vector. For pressure, It is the identity matrix. For dynamic viscosity, The coefficient of thermal expansion is The melting temperature is... It is gravitational acceleration. This is the Darcy damping force, used to simulate the molten state.

[0060] The parameters of the liquid material are as follows: density 3030 kg / m³, specific heat capacity 1260 J / (kg·K), thermal conductivity 2.05 W / (m·K), dynamic viscosity decreases with increasing temperature (0.584 Pa·s at 2323 K and 0.264 Pa·s at 2623 K), latent heat of fusion 2958 J / g, and latent heat of vaporization 4891 J / g.

[0061] Experimental and simulation comparison verification: The morphology and temperature distribution obtained by simulation were compared with the experimental results. The simulation results were consistent with the experimental morphology and characteristic size trends, and the relative errors were all less than 15%.

[0062] Example

[0063] The present invention will be further illustrated by the following examples.

[0064] Example 1: A repetition frequency of 3000 Hz, a peak power of 59.23 W, a duty cycle of 40%, and an irradiation time of 3 s were used. The results are as follows: Figure 2 As shown: A central thermal expansion bulge with a height of about 40µm is formed in the center, and an annular melting depression with a width of about 100µm and a depth of about 5µm is formed around it. There are resolidification ridges at the edge of the melting pit.

[0065] Example 2: A repetition frequency of 2000 Hz, a peak power of 59.23 W, a duty cycle of 20%, and an irradiation time of 3 s were used. The results are as follows: Figure 3 As shown: the central thermal expansion bulge is approximately 25µm high, and a ring-shaped thermal expansion bulge appears approximately 200µm from the center, with a flat region in between. This phenomenon is caused by the energy redistribution resulting from the deflection of the laser light by the central bulge.

[0066] Example 3: With a fixed repetition frequency of 3000Hz and a duty cycle of 40%, the peak power was varied. The results are as follows: Figure 4 As shown, when the peak power increases from 42W to 60W, the center height increases from 3µm to 45µm; after the peak power exceeds 60W, the center height decreases rapidly, turning negative at 84W, with a pit depth of approximately 20µm. This inflection point corresponds to the material's transition from being dominated by thermal expansion to being dominated by melting.

[0067] Example 4: With a fixed peak power of 59.23W and a duty cycle of 40%, the repetition frequency was changed. The results are as follows. Figure 5 As shown, when the frequency increases from 1000Hz to 2000Hz, the height of the central bulge increases from 5µm to 40µm, and the diameter of the expansion region increases from 200µm to 400µm; above 2000Hz, both the bulge height and diameter decrease. Below 1000Hz, shallow molten pits predominate, while above 3000Hz, deep and smooth molten pits form.

[0068] Example 5: Simulation was performed under the operating conditions of a repetition frequency of 1000Hz, peak power of 59.23W, and duty cycle of 40%. The results are as follows: Figure 6 As shown: After 120ms of irradiation, the center temperature reached 1010K, and the peak radial and circumferential compressive stresses were approximately 1340MPa, exceeding the compressive strength of sapphire at this temperature (approximately 400MPa), causing plastic flow in the material and forming protrusions. The axial stress was close to 0.

[0069] Example 6: Simulation was performed under the operating conditions of a repetition frequency of 4000Hz, a peak power of 59.23W, and a duty cycle of 40%. The results are as follows: Figure 7 As shown: After 150 ms of irradiation, the center temperature reaches the melting point, and a flow velocity field of magnitude 10 begins to appear from the center to the edge. - 4m / s; with increasing irradiation time, the central depression deepens and the edge accumulation increases; after 478 ms, a distinct molten pit forms, with a depth of approximately 100 µm and an edge protrusion height of approximately 50 µm. The flow is dominated by the Marangoni effect.

[0070] Through comparison with the above embodiments and simulations, it is demonstrated that the method of the present invention is repeatable and controllable, and the simulation results are consistent with the experimental morphology and feature size trends, with relative errors all less than 15%. This provides a reliable process window and theoretical basis for sapphire CO2 laser thermal melting processing. The preferred parameter window is: repetition frequency of 2000Hz to 3000Hz, peak power of 59W to 70W, and duty cycle of 40%, which can stably obtain a composite structure with a central thermal expansion protrusion height of 20µm to 45µm and an annular melting depression depth of 2µm to 10µm.

[0071] The technical features of the above embodiments can be combined in any way. For the sake of brevity, not all possible combinations of the technical features in the above embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0072] The embodiments described above are merely illustrative of several implementation methods of this application, and while the descriptions are specific and detailed, they should not be construed as limiting the scope of this application. It should be noted that those skilled in the art can make various modifications and improvements without departing from the concept of this application, and these modifications and improvements all fall within the protection scope of this application. Therefore, the protection scope of this application should be determined by the appended claims.

Claims

1. A method for forming a central thermal expansion protrusion and annular melting depression on the surface of sapphire by CO2 laser irradiation, characterized in that, Includes the following steps: A pulsed CO2 laser with a wavelength of 10.6 μm was used to focus the laser beam and irradiate it vertically onto the surface of a single-crystal sapphire sample. The repetition frequency of the laser was adjusted to 1000 Hz to 4000 Hz, the peak power to 42 W to 85 W, the duty cycle to 20% to 40%, and the irradiation time to 1 s to 5 s, so that a central thermal expansion protrusion and a ring-shaped melting depression were formed on the sapphire surface. The two-dimensional and three-dimensional morphology of the irradiated area was observed using an optical microscope and a white light interferometer. A two-dimensional axisymmetric geometric model was established, and a thermo-solid coupling model and a thermo-fluid coupling model were constructed. Laser parameters and thermal property parameters of sapphire were set to be consistent with the aforementioned laser parameters. The temperature field control equation, stress field control equation and Navier-Stokes equation were solved. The morphology output by simulation was compared and verified with the morphology obtained by observation.

2. The method according to claim 1, characterized in that, The single-crystal sapphire sample is a C-face sapphire, A-face sapphire, or M-face sapphire, and the sample thickness is not less than 1 mm.

3. The method according to claim 1, characterized in that, The radius of the laser focusing spot is 0.6mm~1.0mm.

4. The method according to claim 1, characterized in that, When the repetition frequency is 2000Hz~3000Hz, the peak power is 59W~70W, and the duty cycle is 40%, a composite structure of a central thermal expansion protrusion and a surrounding annular molten depression is formed on the sapphire surface. The height of the central thermal expansion protrusion is 20µm~45µm, and the depth of the annular molten depression is 2µm~10µm.

5. The method according to claim 1, characterized in that, When the repetition frequency is 2000Hz, the peak power is 59W, and the duty cycle is 20%, a double-protrusion structure is formed on the sapphire surface, consisting of a central thermal expansion protrusion and a surrounding annular thermal expansion protrusion.

6. The method according to claim 1, characterized in that, The thermo-solid coupling model is used to analyze the stress distribution during the thermal expansion stage. Calculations show that radial and circumferential stresses are mainly compressive stresses. When the temperature exceeds 1000K, the compressive stress can reach 1340MPa, which exceeds the compressive strength of sapphire at 1000K, forcing the softened material to flow upward plastically and form protrusions.

7. The method according to claim 1, characterized in that, The thermal-fluid coupling model considers the change in surface tension with temperature and the Marangoni effect. The molten material migrates from the central high-temperature, low-surface-tension region to the edge low-temperature, high-surface-tension region, forming a molten pit morphology with a central depression and edge accumulation.